Zakat Transformation in Improving Economic Welfare in the Digital Era - Sandi, Rovita Sandi; Iqbal , Iqbal Dwi Alamsyah (Alhamdulillah : Jurnal Agama Islam, 2023)
Digital transformation in zakat management has brought significant changes in efficiency, transparency, and its impact on the economic welfare of the community. This study aims to explore the impact of implementing digital technology in zakat collection and distribution, and how it affects the improvement of the social and economic welfare of mustahik. The results of the study show that after the implementation of digitalization, the amount of zakat collection increased threefold, the number of mustahik reached also increased rapidly, and the speed of zakat distribution decreased drastically. In addition, the operational costs of zakat management decreased by 50%, while the level of transparency and accountability increased significantly. The increase in user satisfaction of digital platforms also reflects the success of digitalization in accelerating distribution and ensuring more efficient and measurable use of zakat. This study recommends that more zakat institutions adopt digital technology and strengthen collaboration between parties to ensure the sustainability and success of digital-based zakat management.